Update of safety profile of bile acid sequestrants: A real-world pharmacovigilance study of the FDA adverse event reporting system. - Wangqi Chen; Yuxia Xie; Qinghua Li; Zhenghui Zhu; Xinyan Li; Hong Zhu (PLoS ONE)
Background Bile acid sequestrants (BASs), including cholestyramine, colestipol, and colesevelam, are widely used in endocrine and gastrointestinal disorders. However, their long-term safety remains under-characterized. This study leveraged real-world pharmacovigilance data to evaluate underreported and subclass-specific adverse events (AEs) associated with BASs. Methods We analyzed 5,286 AE reports related to BASs from the FDA Adverse Event Reporting System (2004-2024) using four disproportionality methods: Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-item Gamma Poisson Shrinker (MGPS). AE signals were assessed at both the System Organ Class (SOC) and Preferred Term (PT) levels. Time-to-onset (TTO) analysis was also performed. Results All three BASs showed prominent gastrointestinal AEs. Cholestyramine was notably associated with oropharyngeal irritation (e.g., throat irritation, ROR = 21.89; oropharyngeal discomfort, ROR = 36.53), while colestipol presented mechanical risks such as dysphagia (ROR = 21.51) and choking (ROR = 67.44). Colesevelam exhibited musculoskeletal toxicity, including myalgia (ROR = 4.74) and muscle spasms (ROR = 3.43). Consensus signals across all methods further revealed novel AEs such as dysgeusia, dental abnormalities, gastroesophageal reflux disease, and fecaloma. TTO analysis showed that most AEs occurred within the first month of therapy, with 15-16% persisting beyond 6 months. Conclusion This large-scale FAERS study updates the safety profiles of BASs, highlighting distinct risk patterns and delayed complications. The findings support personalized monitoring strategies that consider both drug-specific characteristics and temporal AE patterns.